Alpha-Actinin 4 Is Associated with Cancer Cell Motility and Is a Potential Biomarker in Non–Small Cell Lung Cancer. Issue 2 (February 2015) - Wang, Ming-Chuan; Chang, Ying-Hua; Wu, Chih-Chieh; Tyan, Yu-Chang; Chang, Hua-Chien; Goan, Yih-Gang; Lai, Wu-Wei; Cheng, Pin-Nan; Liao, Pao-Chi
Abstract : Background: Differential expression and secretion of alpha-actinin 4 (ACTN4) in the lung cancer cell lines CL1-0 and CL1-5 have been reported in previous proteomic studies. The aim of this study is to investigate the functional properties of the ACTN4 protein in non–small-cell lung cancer (NSCLC) cells and evaluate its clinical importance. Methods: We used RNA interference to knock down and overexpress ACTN4 protein to evaluate the effects of this intervention on cancer cell invasion and migration, as well as on microscopic cellular morphology. Furthermore, we examined by immunohistochemistry the expression of ACTN4 protein in tissue samples at different stages of lung cancerand compared the protein levels of ACTN4 in blood plasma samples from patients with histologically confirmed lung cancer and healthy controls. Results: CL1-5 cell motility was significantly suppressed by the knockdown of ACTN4 protein. The morphology of CL1-5 cells changed from a predominantly mesenchymal-like shape into a globular shape in response to ACTN4 protein knockdown. A quantitative immunohistochemical assessment of lung cancer tissues revealed that ACTN4 protein level was considerably higher in cancerous tissues than in the adjacent normal ones, and the area under the receiver operating characteristic curve was 0.736 ( p < 0.001). According to an enzyme-linked immunosorbent assay, the plasma levels of ACTN4 protein were significantly different between cancer patients and healthy controls, and the areas under the receiver operating characteristic curves were 0.828 and 0.909, respectively, for two independent cohorts ( p < 0.001). Conclusions: We demonstrate that the knockdown of ACTN4 protein inhibited cell invasion and migration. These results suggest that ACTN4 is associated with lung cancer cell motility. Thus, the level of ACTN4 in cancerous tissue and plasma is related to the presence of lung cancer.